Kepuasan Pernikahan Ditinjau dari Berpacaran dan Tidak Berpacaran - Iis Ardhianita; Budi Andayani (Faculty of Psychology, Universitas Gadjah Mada, 2005)
Getting married is perceived as an important phase in human life‐cycle. Just like fashion, marriage has also its own trend or mode. In Indonesia the legend of Siti Nurbaya illustrating a kind of marital arrangement in, at least, the first half of the past century. Such a trend in marriage is any more popular these days. Young people today mostly prefer to marry their own choices, those already bond in engagement or girl or boy friends they already mate. Another kind of trend has appeared recently. Some moslems prefer to marry without the phase of dating or engagement. Some even marry ones chose, or arranged by their ustadz (spiritual leader). The purpose of this study is to find out whether a difference in the premarital relationship(with versus without engagement or dating) affect couples’ marital satisfaction. The result shows that there is a very significant difference in marital satisfaction between dating and non‐dating couples. Explanation upon the phenomenon discussed. Keywords: marital satisfaction, dating and non dating couples